Understanding the Operation Called Comparison - Wivian Weller (Universidade Federal do Rio Grande do Sul, 2017)
Cultural comparison in social sciences was seen for a long time as a scientific procedure to uncover hidden structures behind the development of societies. Based on contributions from Friedrich Tenbruck and Joachim Matthes, the first part of the article comprises a critical analysis of this understanding of comparison and comparative methods. The second part presents two international research studies with an emphasis on the methodological procedures and the reasons for the development of both studies as well as the experiences gained from these projects. The significance of a comparative study is not only in the ability to understand unknown situations and realities, but also in finding out what we did not know about ourselves.